Strengthening the success beyond zero on HIV infection through PITC In Private Hospitals. - ABANJA WILLIAM OTIENO. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Background: HIV management is one of the medical services offered at the Mater hospital’s two HIV management clinics: The Mater Total Care Clinic (MTCC-consultant) and Mater Comprehensive Care Clinic (MCCC-sponsored). MCCC runs an integrated VCT to walk-in clients. The hospital serves about 5440 and 440 patients a month at its OPD and IPD respectively. An average of 178 patients receives medical services at Accident & Emergency unit (A&E) every day. Most of these clients are corporate. Corporate patients are mostly reluctant for HIV screening and do not prefer findings to be included in their medical reports. Client Initiated HTC to such clients in private hospitals may mostly seem unfruitful. With this background, MCCC felt a need to evaluate the impact and expand its HIV services at A&E through Provider Initiated Testing & Counselling (PITC) so as to reach more clients. Objectives: To use a friendly PITC approach to every client at A&E. To link HIV positive clients to care. To offer on-going psychosocial & emotional support and results oriented retention strategy Method: A survey trial. Provision of brochures at registrations desk, customised friendly fit messages that capture benefits available with uptake of HIV testing (RAPID RESULTS), packaged care, treatment and support following results, active client navigation to testing and treating stations, linking client to mentorship and counselling support initiatives and Aided Partner Notification program. Results: Out of 660 clients tested in a month at A& E, 100% positive clients successfully linked to care leading to increased number of family testing and partner testing, increased uptake of staff testing as well as general male testing (from 20% - 92) and 95% self-initiated testing. Conclusion and Recommendation: Refined strategies, a kit necessary to escalate HIV testing to capture cooperate clientele in Private Hospitals. Other leading private hospitals can embrace similar small test of change. This will ensure success towards beyond zero HIV, stigma, and deaths especially to clients of social status in private hospitals.